Diagnostic accuracy of D-dimer to detect left atrial thrombus in patients with atrial fibrillation: a systematic review and meta-analysis. (14th October 2021) - Diaz-Arocutipa, C; Gonzales-Luna, A.C; Branez-Condorena, A; Hernandez, A.V
Abstract: Background: There is limited evidence on the use of biomarkers to diagnose left atrial thrombus in atrial fibrillation. Purpose: We evaluated the diagnostic accuracy of D-dimer to detect left atrial thrombus in patients with atrial fibrillation. Methods: We searched four electronic databases from inception to December 16, 2020 for observational studies evaluating diagnostic accuracy of D-dimer. Reference standard was left atrial thrombus detected by transesophageal echocardiography. Study quality was assessed with the QUADAS-2 tool. We performed a bivariate random-effects meta-analysis to calculate the pooled sensitivity and specificity with their 95% confidence intervals (95% CI). In addition, a summary receiver operating characteristic curve and optimal cut-off were estimated. Results: Eleven cross-sectional studies involving 4380 patients were included. The mean age ranged from 49.8 to 74.1 years and 70% of patients were men. Left atrial thrombus was present in 7% of cases. In seven studies, the pooled sensitivity of D-dimer at 500 ng/mL was 53% (95% CI, 26–79%) and the pooled specificity was 92% (95% CI, 80–97%). The pooled sensitivity of age-adjusted D-dimer was 35% (95% CI, 18–57%) and the pooled specificity was 100% (95% CI, 100–100%) in two studies. The optimal cut-off was 390 ng/mL in 10 studies with a pooled sensitivity of 68% (95% CI, 44–85%) and a pooled specificity of 73% (95% CI, 54–86%). The risk of bias was low or unclear for all domains. Concerns regarding applicability were generally low for almost all studies Conclusion: Our meta-analysis suggests that D-dimer has the potential to be useful to the detection of left atrial thrombus in patients with atrial fibrillation. Funding Acknowledgement: Type of funding sources: None.